S-nitrosylation of proteins with nitric oxide: synthesis and characterization of biologically active compounds. - Stamler, J S (1992)
Endothelium-derived relaxing factor (EDRF) activity has been attributed to the highly labile nitric oxide radical (NO). In view of the fact that the plasma and cellular milieux contain reactive species that can rapidly inactivate NO, it has been postulated that NO is stabilized by a carrier molecule that preserves its biological activity. Reduced thiol species are candidates for this role, reacting readily in the presence of NO to yield biologically active S-nitrosothiols that are more stable than NO itself. Because sulfhydryl groups in proteins represent an abundant source of reduced thiol in biologic systems, we examined the reaction of several sulfhydryl-containing proteins of diverse nature and function upon exposure to authentic NO and EDRF. We demonstrate that S-nitroso proteins form readily under physiologic conditions and possess EDRF-like effects of vasodilation and platelet inhibition. These observations suggest that S-nitrosothiol groups in proteins may serve as intermediates in the cellular metabolism of NO and raise the possibility of an additional type of cellular regulatory mechanism.